Advances in Swarm and Computational Intelligence : 6th International Conference, ICSI 2015 held in conjunction with the Second BRICS Congress, CCI 2015, Beijing, China, June 25-28, 2015, Proceedings, Part III - Tan, Ying.; Shi, Yuhui; Buarque, Fernando; Gelbukh, Alexander; Das, Swagatam; Engelbrecht, Andries; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book and its companion volumes, LNCS volumes 9140, 9141 and 9142, constitute the proceedings of the 6th International Conference on Swarm Intelligence, ICSI 2015 held in conjunction with the Second BRICS Congress on Computational Intelligence, CCI 2015, held in Beijing, China in June 2015. The 161 revised full papers presented were carefully reviewed and selected from 294 submissions. The papers are organized in 28 cohesive sections covering all major topics of swarm intelligence and computational intelligence research and development, such as novel swarm-based optimization algorithms and applications; particle swarm opt8imization; ant colony optimization; artificial bee colony algorithms; evolutionary and genetic algorithms; differential evolution; brain storm optimization algorithm; biogeography based optimization; cuckoo search; hybrid methods; multi-objective optimization; multi-agent systems and swarm robotics; Neural networks and fuzzy methods; data mining approaches; information security; automation control; combinatorial optimization algorithms; scheduling and path planning; machine learning; blind sources separation; swarm interaction behavior; parameters and system optimization; neural networks; evolutionary and genetic algorithms; fuzzy systems; forecasting algorithms; classification; tracking analysis; simulation; image and texture analysis; dimension reduction; system optimization; segmentation and detection system; machine translation; virtual management and disaster analysis.
Novel swarm-based optimization algorithms and applications -- Particle swarm optimization -- Ant colony optimization -- Artificial bee colony algorithms -- Evolutionary and genetic algorithms -- Differential evolution -- Brain storm optimization algorithm -- Biogeography based optimization -- Cuckoo search -- Hybrid methods -- Multi-objective optimization -- Multi-agent systems and swarm robotics -- Neural networks and fuzzy methods -- Data mining approaches -- Information security -- Automation control -- Combinatorial optimization algorithms -- Scheduling and path planning -- Machine learning -- Blind sources separation -- Swarm interaction behavior -- Parameters and system optimization -- Neural networks -- Evolutionary and genetic algorithms -- Fuzzy systems -- Forecasting algorithms -- Classification -- Tracking analysis -- Simulation -- Image and texture analysis -- Dimension reduction -- System optimization -- Segmentation and detection system -- Machine translation -- Virtual management and disaster analysis.
Keywords: Computer software; Electronic data processing; Data mining; Computer simulation; Artificial intelligence; Algorithm Analysis and Problem Complexity; Numeric Computing; Data Mining and Knowledge Discovery; Simulation and Modeling; Artificial Intelligence